Comparing TEE‐ vs Non–TEE‐guided cardioversion of atrial fibrillation: The ENSURE‐AF trial. (30th March 2020) - Kozieł, Monika; Merino, Jose L.; De Caterina, Raffaele; Huber, Kurt; Jin, James; Melino, Michael; Goette, Andreas; Lip, Gregory Y. H.; ,
Abstract: Background: ENSURE‐AF (NCT 02072434) assessed therapy with edoxaban vs enoxaparin‐warfarin in patients with nonvalvular atrial fibrillation (AF) undergoing elective electrical cardioversion (ECV). Objectives: To evaluate clinical features and primary efficacy (composite of stroke, systemic embolic events, myocardial infarction and cardiovascular mortality during study period) and safety endpoints (composite of major and clinically relevant nonmajor bleeding during on‐treatment period) in patients awaiting ECV of AF with a transesophageal echocardiography (TEE)‐guided vs a non–TEE‐guided strategy. Methods: In this prospective, randomized, open‐label, blinded endpoint study, 2199 patients were randomized to edoxaban 60 mg once‐daily (30 mg for creatinine clearance 15‐50 mL/min, weight ≤60 kg and/or concomitant use of P‐glycoprotein inhibitor) or enoxaparin‐warfarin. Primary efficacy endpoint and safety endpoint were reported. Associates of TEE use, efficacy endpoint and safety endpoint were explored using multivariable logistic regression. Results: In total, 589 patients from the edoxaban stratum and 594 from the enoxaparin‐warfarin stratum were allocated to the TEE‐guided strategy. Primary efficacy was similar regardless of TEE approach ( P = .575). There were no significant differences in bleeding rates, regardless of TEE approach ( P = .677). Independent predictors of TEE use were as follows: history of ischaemic stroke/ transient ischaemic attack, hypertension and valvular heart disease. Mean CHA2 DS2 VASc and HAS‐BLED score were independent predictors of the efficacy endpoint whilst mean age was an independent predictor of the safety endpoint. Conclusions: Thromboembolic and bleeding events were not different between patients undergoing TEE‐guided strategy and in those undergoing an optimized conventional anticoagulation approach for ECV of AF.